Genetically proxied gut microbiota, gut metabolites with risk of epilepsy and the subtypes: A bi-directional Mendelian randomization study - Ouyang, Yuzhen; Chen, Yu; Wang, Ge; Song, Yanmin; Zhao, Haiting; Xiao, Bo; Yang, Zhuanyi; Long, Lili (Frontiers in Molecular Neuroscience, 2022)
Background: An increasing number of observational studies have revealed an association between the gut microbiota, gut metabolites, and epilepsy. However, this association is easily influenced by confounders such as diet, and the causality of this association remains obscure. Methods: Aiming to explore the causal relationship and ascertain specific gut microbe taxa for epilepsy, we conducted a bi-directional Mendelian randomization (MR) study based on the genome-wide association study (GWAS) data of epilepsy from the International League Against Epilepsy, with the gut microbiota GWAS results from MiBioGen and summary-level GWAS data of gut microbiota-dependent metabolites trimethylamine N-oxide and its predecessors. Results: Nine phyla, 15 classes, 19 orders, 30 families, and 96 genera were analyzed. A suggestive association of host-genetic-driven increase in family Veillonellaceae with a higher risk of childhood absence epilepsy (odds ratio [OR]: 1.033, confidential interval [CI]: 1.015–1.051, PIVW=0.0003), class Melainabacteria with a lower risk of generalized epilepsy with tonic-clonic seizures (OR=0.986, CI=0.979–0.994, PIVW=0.0002), class Betaproteobacteria (OR=0.958, CI=0.937–0.979, PIVW=0.0001) and order Burkholderiales (OR=0.960, CI=0.937–0.984, PIVW=0.0010) with a lower risk of juvenile myoclonic epilepsy were identified after multiple-testing correction. Our sensitivity analysis revealed no evidence of pleiotropy, reverse causality, weak instrument bias, or heterogeneity. Conclusions: This is the first MR analysis to explore the potential causal relationship between the gut microbiota, metabolites, and epilepsy. Four gut microbiota features (two class levels, one order level, and one family level) were identified as potential interventional targets for patients with childhood absence epilepsy, generalized epilepsy with tonic-clonic seizures, and juvenile myoclonic epilepsy. Previous associations in numerous observational studies may have been interfered with by confounders. More rigorous studies are needed to ascertain the relationship between the gut microbiota, metabolites, and epilepsy.